How stem cell composition in bone marrow aspirate relates to clinical outcomes when used for cervical spine fusion - Chaput, Christopher D. (PLoS One, 2018)
Anterior cervical discectomy and fusion (ACDF) is performed to relieve pain caused by degenerative disk disease and nerve obstruction. As an alternative to bone graft, autologous concentrated bone marrow aspirate (CBMA) is used to achieve vertebral fusion with a satisfactory success rate. This has been attributed in part to bone marrow-resident mesenchymal stromal cells (MSCs) with the capacity to differentiate into osteoblasts and generate bone tissue. To date, there has been no study comparing cellular yields, MSC frequencies and their osteogenic potential with ACDF outcome. Patients (n = 24) received ACDF with CBMA and allograft bone matrix. Colony forming unit fibroblast (CFU-F) and CFU-osteoblasts (CFU-O) assays were performed on CBMA samples to enumerate MSCs (CFU-F) and osteogenic MSCs (CFU-O). CFUs were normalized to CBMA volume to define yield and also to mononuclear cells (MNC) to define frequency. After 1-year, fusion rates were good (86.7%) with pain and disability improved. There was a negative relationship between MNC and CFU-F measurements with age of patient and CFU-Os negatively correlated with age in females but not males. Tobacco use did not affect CBMA but was associated with poorer clinical outcome. Surprisingly, we found that while high-grade fusion was not associated with CFU-O, it correlated strongly (p<0.0067) with CBMA containing the lowest frequencies of CFU-F (3.0x10(-6)–5.83x10(-5) CFU-F/MNC). MNC levels alone were not responsible for the results. These observations suggest that osteogenesis by human bone marrow is controlled by homeostatic ratio of MSCs to other cellular bone marrow components rather than absolute level of osteogenic MSCs, and that a lower ratio of MSCs to other cellular components in marrow tends to predict effective osteogenesis during ACDF. The results presented herein challenge the current dogma surrounding the proposed mechanism of MSCs in bone healing.